2015
DOI: 10.1016/j.parkreldis.2015.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Clinically meaningful parameters of progression and long-term outcome of Parkinson disease: An international consensus statement

Abstract: Parkinson disease (PD) is associated with a clinical course of variable duration, severity, and a combination of motor and non-motor features. Recent PD research has focused primarily on etiology rather than clinical progression and long-term outcomes. For the PD patient, caregivers, and clinicians, information on expected clinical progression and long-term outcomes is of great importance. Today, it remains largely unknown what factors influence long-term clinical progression and outcomes in PD; recent data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 100 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…Recent data showed that the main motor symptoms impacting the health-related QoL of patients with PD include dyskinesia, motor fluctuations, axial impairment, and freezing of gait [ 2 ]. Regarding non-motor symptoms (NMS), depression, dementia, psychosis, cognitive impairment, apathy, and sleep disorders were found to be the most common determinants in reducing QoL and increasing disability [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data showed that the main motor symptoms impacting the health-related QoL of patients with PD include dyskinesia, motor fluctuations, axial impairment, and freezing of gait [ 2 ]. Regarding non-motor symptoms (NMS), depression, dementia, psychosis, cognitive impairment, apathy, and sleep disorders were found to be the most common determinants in reducing QoL and increasing disability [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results highlight the importance of jointly measuring the complex interplay between motor and cognitive skills in PD [4,5], not only in multitask settings but also in single condition performance. Only tasks that impose motor-cognitive hybrid demands seem to be able to detect disability levels in single condition and performance worsening in concurrent condition (i. e., dual or triple), even when cognitive decline is controlled.…”
Section: Discussionmentioning
confidence: 73%
“…However, cognitive decline usually coexists with motor impairment as a consequence of the neurodegenerative progression [2]. Despite the relationship between cognitive and motor impairments in PD [3], cognitive performance is usually measured regardless of the motor impairment or as with other nonmotor features of the illness, does not receive adequate attention [4]. e interaction between the motor and cognitive components seems to determine the functional capacity and should be considered simultaneously in the evaluation of the progression of PD [5].…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis was put on harmonization of the datasets with ongoing international cohort studies for comparability and cross validation, thereby increasing statistical power of the planned analyses. Therefore, the diagnostic criteria and scales applied in our study, have been aligned with already existing international cohort programs, e.g., DeNoPa ( Mollenhauer et al, 2013 ), Oxford PD Centre (OPDC) ( Lawton et al, 2015 ); PPMI ( Marek et al, 2011 ), GEoPD ( Puschmann et al, 2015 ), as described previously ( Lerche et al, 2015 ). Harmonization rates are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%